Twain's Omissions : Exploring the Gaps as Textual Context. - Martin, Gretchen (Cambridge Scholars Publishing, 2013)
Mark Twain utilized a unique literary device throughout his fiction by routinely omitting or suspending crucial information in terms of plot, character portraits, descriptive events, chronology, and other aspects from his texts. Twain often introduces characters with very few details regarding their personal histories; while, other information is withheld in terms of the narrative's chronology or not addressed at all, thus producing gaps in the narrative. For example, Twain does not provide a ...